Atratividade e competitividade no investimento direto estrangeiro na infraestrutura do transporte ferroviário - Cruz, Nidi Andreia da (2021)
For a long time, the rail transport sector in Brazil is without investments and, even, forgotten. However, when considering the globalization scenario, it is noted that the growth of this sector is necessary or even mandatory in the coming years. For this growth to occur in the sector, since there is a limitation of resources from the public sector, there is the importance of receiving investments from the private sector, in particular resources coming from abroad through foreign direct investment (FDI). This dissertation aims to analyze the relationships between the indicators of attractiveness and competitiveness with FDI in the infrastructure segment, particularly in Rail Transport. For this, as a theoretical basis the Transaction Costs Theory (TCT) was used, in particular for the aspects that deal with risky transactions and contracts, as well as the Institutional Theory that involves the institutional aspects of the host country related to the attraction of FDI mainly in emerging markets. It is not yet clear in the literature how infrastructure FDI can be related to the indicators of attractiveness and competitiveness. The contribution of this research was to investigate the correlation of the FDI with the indicators of attractiveness of the Doing Business Report and of competitiveness of the Global Competitiveness Report. For this, the mixed method with a quantitative approach was used with an analysis of the secondary data of attractiveness, competitiveness and FDI, as well as qualitative based on eleven in-depth interviews with professionals and actors in the area. The results revealed convergence between the quantitative and qualitative analyzes showing that the factors of attractiveness and competitiveness have an impact, but they are not the only predominant factors for the FDI decision. It was possible to identify in the interviews that investors consider the factor of relevant market opportunity in the decision-making process when investing in an emerging country like Brazil. Additionally, it showed that the experience of acting in the Brazilian market is a prominent factor in determining the way of entering the market through partnerships or acquisition. These results provided important academic and managerial contributions to better understand the FDI in infrastructure in Brazil as well as proposals to be verified in future research involving other contexts in emerging countries.